Knowledge, Attitude and Practice Toward COVID-19: A Cross-Sectional Study of Staff in China-Guinea Friendship Hospital, Guinea - Ji, Wenyan; Camara, M'Bemba Abdoulaye; Xia, Jinggang; Ma, Xiaobo; Chen, Xintong; Liu, Ying (Frontiers in Public Health, 2022)
Background: The purpose of this study was to assess the level of knowledge, attitude and practice of COVID-19 among staff in China-Guinea Friendship Hospital, and to confirm the effect of nosocomial infection management. Methods: This cross-sectional study was conducted in December 2021. Information on sociodemographic data, knowledge, attitude and practices related to COVID-19 was collected through a self-administered questionnaire. Results: One hundred and forty-three employees participated in the survey, with a response rate of 99.31% and a vaccination rate of 95.10%. The average knowledge score of COVID-19 was 8.39±1.3 point (10 point in total), without significant differences between subgroups in the characteristics of each population (P>0.05); more than 80% of the participants had a positive attitude, and 72.03% 93.01% of the participants could take appropriate preventive practices in different environments such as hospital, outdoor or home. Conclusion: The staff of the China-Guinea Friendship Hospital has good knowledge, positive attitude and appropriate preventive practices associated with COVID-19. It can be considered that the current nosocomial infection management is active and effective.